Community Perilaku Masyarakat dalam Mengelola Sampah Rumah Tangga di Distrik Manokwari Timur Kabupaten Manokwari - yosmina waliki; Ihwan Tjolli; Hugo Warami (Program Pascasarjana Universitas Papua, 2020)
This study aims to (1) determine the behavior of the community in managing household waste in Manokwari Timur District, Manokwari Regency, (2) to analyze the factors that influence people's behavior in managing household waste. This research was conducted in Manokwari Regency, West Papua Province. The research method used is descriptive quantitative with data analysis using multiple regression analysis. The results showed: (1) The overall behavior of the community in managing household waste in East Manokwari District (65.5%) was in the sufficiently supportive category. Meanwhile, as many as 34.9% are in the unsupported category, (2) The results of multiple linear regression analysis show that the variables of Formal Education, Guidance of Community Leaders, Infrastructure and Knowledge together have an effect on Community Behavior in Household Waste Management. The results of the partial relationship test show that the variables of formal education have a very significant effect on community behavior in household waste management; The variable of direction of community leaders has a significant effect on community behavior in managing household waste; infrastructure and knowledge variables did not affect people's behavior in household waste management.